High Thermoelectric Performance of New Rhombohedral Phase of GeSe stabilized through Alloying with AgSbSe2. Issue 45 (5th October 2017) - Huang, Zhiwei; Miller, Samuel A.; Ge, Binghui; Yan, Mingtao; Anand, Shashwat; Wu, Tianmin; Nan, Pengfei; Zhu, Yuanhu; Zhuang, Wei; Snyder, G. Jeffrey; Jiang, Peng; Bao, Xinhe
Abstract: GeSe is a IV–VI semiconductor, like the excellent thermoelectric materials PbTe and SnSe. Orthorhombic GeSe has been predicted theoretically to have good thermoelectric performance but is difficult to dope experimentally. Like PbTe, rhombohedral GeTe has a multivalley band structure, which is ideal for thermoelectrics and also promotes the formation of Ge vacancies to provide enough carriers for electrical transport. Herein, we investigate the thermoelectric properties of GeSe alloyed with AgSbSe2, which stabilizes a new rhombohedral structure with higher symmetry that leads to a multivalley Fermi surface and a dramatic increase in carrier concentration. The zT of GeAg0.2 Sb0.2 Se1.4 reaches 0.86 at 710 K, which is 18 times higher than that of pristine GeSe and over four times higher than doped orthorhombic GeSe. Our results open a new avenue towards developing novel thermoelectric materials through crystal phase engineering using a strategy of entropy stabilization of high‐symmetry alloys. Abstract : Energy conversion : The thermoelectric performance of GeSe is dramatically enhanced by an alloying‐induced structural phase transition. A zT value of 0.86 at 710 K is achieved for GeAg0.2 Sb0.2 Se1.4 . The results open a new avenue towards developing novel thermoelectric materials through crystal phase engineering using a strategy of entropy stabilization of high‐symmetry alloys.